Anti-Staphylococcus aureus Activity and Structural Characterization of Rationally Designed Peptides - Lorenza Artesani; Mariana Gallo; Laura Giovati; Francesca Maria Bisignano; Elena Ferrari; Lara M. Castronovo; Stefania Conti; Francesco Santoro; Thelma A. Pertinhez; Tecla Ciociola (Antibiotics)
Background/Objectives: Microbial infections represent a significant threat to public health due to the emergence and spread of antimicrobial resistance. Adjunctive and alternative therapeutic strategies are explored to tackle this issue, including the use of natural or synthetic antimicrobial peptides. Previous research showed that antibody-derived peptides possess antimicrobial, antiviral, and immunomodulatory properties. This study aimed to characterize newly designed antibody-derived peptides and evaluate their effectiveness against representative strains of Staphylococcus aureus, including drug-resistant isolates. Methods: Colony-forming unit assays and confocal microscopy studies were performed to evaluate peptide activity against planktonic microbial cells. Cytotoxicity tests were performed on THP-1 human monocytic cells. Circular dichroism (CD) and nuclear magnetic resonance (NMR) were employed for the conformational characterization of peptides. Results: The half-maximal effective concentrations of the peptides against bacterial reference strains and drug-resistant isolates ranged from 0.17 to 18.05 µM, while cytotoxic effects were not observed against mammalian cells. A killing kinetics analysis and observation by confocal microscopy of the interaction between peptides and bacteria suggested a mechanism of action involving membrane perturbation. CD studies showed that all peptides predominantly exhibit a random coil arrangement in aqueous solution. NMR spectroscopy revealed that the most active peptide adopts a helical conformation in the presence of membrane mimetics. Conclusions: The structural characterization and evaluation of the newly designed peptides’ antimicrobial activity may lead to the selection of a candidate to be further studied to develop an alternative treatment against microbial infections caused by drug-resistant strains.